Die Wirtschaftssanktionen als die Mittel der internationalen Druck während der russisch-ukrainischen Krise. Majandussanktsioonid kui rahvusvaheline survemeede: kui suured on eduvõimalused Venemaa-Ukraina kriisi puhul - Veebel, Viljar; Markus, Raul (Estonian Discussions on Economic Policy, 2015)
To stop the conflict in Ukraine, in 2014 the European Union (EU), the United States and others western countries have introduced targeted sanctions against Russia, which where followed by countermeasures imposed by Russia. While the USA and the EU (including Estonia) are expecting that Russia will be unable to adapt to the pressure of sanctions at least in mid-term, Russia expects to last longer than Ukraine to get tactical advantage. The aim of the research is to analyse whether sanctions against Russia have the economic potential to work. The authors suggest that based both on theory and previous practical experience, the direct economic impact of the EU-sanctions is relatively modest. However, the indirect pressure on the Russian economy exercised by the decrease in oil prices in the world market and the reaction of the financial markets, combined with the sanctions have at least potential to lead to the acceptable political solution from the perspective of the EU and the USA